Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) Seroprevalence and Risk Factors Among Oligo/Asymptomatic Healthcare Workers: Estimating the Impact of Community Transmission. (13th December 2020) - Costa, Silvia Figueiredo; Giavina-Bianchi, Pedro; Buss, Lewis; Mesquita Peres, Carlos Henrique; Rafael, Mayra Matias; dos Santos, Lanuse Garcia Neves; Bedin, Anderson Aparecido; Francisco, Maria Cristina Peres Braido; Satakie, Fatima Mitie; Jesus Menezes, Maria Aparecida; Dal Secco, Ligia Maria; Rodrigues Caron, Deyse Mayara; et al.
Abstract: We evaluated the seroprevalence of SARS-CoV-2 and risk factors among 4987 oligo/asymptomatic healthcare workers; seroprevalence was 14% and factors associated with SARS-CoV-2 infection were lower educational level (aOR, 1.93; 95% CI, 1.03–3.60), using public transport to work (aOR, 1.65; 95% CI, 1.07–2.62), and working in cleaning or security (aOR, 2.05; 95% CI, 1.04–4.03).